Buttersingles - Butterfingers; Bong; EMI (Malaysia). (Kuala Lumpur : EMI (Malaysia), 1997)
Contains three tracks of rock songs.
CD 1 : Fire is a curse / (5:10) -- E / (3:29) -- Vio-pipe / (2:52).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English -- Malaysia; Rock music